Alokasi biaya bersama dalam menentukan harga pokok produksi Joint Product pada Victoria Bakery - Mekutika, Maria Carolina; Pusung, Rudy J.; Rundengan, Fanda D. P. (Yayasan Widyantara Nawasena Raharja, 2025)
Victoria Bakery is a small-scale home industry that produces a variety of breads and cakes, catering to both online and offline markets. Accurate allocation of joint costs is essential in determining the Cost of Goods Sold (COGS), as it reflects the actual costs incurred during the transformation of raw materials into finished goods. Joint costs refer to production expenses shared across multiple products that are generated simultaneously in a single process. This study aims to analyse the allocation of joint costs in determining the COGS at Victoria Bakery. A qualitative research method with a case study approach was employed, utilizing primary data obtained through interviews and documentation. The findings reveal that Victoria Bakery sets a selling price of IDR 10,000 per package for original thick loaf bread and IDR 5,000 per package for chocolate bread. The study applies the relative sales value method to allocate joint costs, resulting in a calculated COGS of IDR 4,683 per package for original loaf bread and IDR 2,514 per package for chocolate bread. These results demonstrate a significant margin between the COGS and the selling prices. The discrepancy is attributed to the lack of a systematic cost calculation method, which has led to inaccurate cost allocation and pricing decisions.